2001
DOI: 10.1590/s1519-566x2001000200012
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de genótipos de tomateiro sobre a biologia e oviposição de Tuta absoluta (Meyrick) (Lep.: Gelechiidae)

Abstract: -This study evaluated, under laboratory conditions, the effect of tomato genotypes (Lycopersicon esculentum, cv. Santa Clara, Stevens and IPA-5; L. hirsutum f. glabratum, line PI 134417 and L. peruvianum line LA 444-1) on biology and oviposition of Tuta absoluta (Meyrick). The least adequate to the insect was LA 444-1 prolonging larval and pupal stages and reducing larval viability, pupal weight, fecundity and adult longevity, when compared to the control ('Santa Clara'). Line PI 134417 increased length of lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
7

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 3 publications
1
3
0
7
Order By: Relevance
“…Considering the larval survival among the wild genotypes, an intermediate resistance level was quantified on S. peruvianum, and greater resistance was measured on S. habrochaites. In accordance with this work, other reports have found higher resistance in wild genotypes compared with commercial cultivars (Thomazini et al, 2001;Proffit et al, 2011;Oliveira et al, 2012). Nonetheless, we here provide further information on the variability that can occur within a single genotype, depending on the accession tested, as we detected a wide range of larval survivals in the accessions of S. habrochaites (Table 2).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Considering the larval survival among the wild genotypes, an intermediate resistance level was quantified on S. peruvianum, and greater resistance was measured on S. habrochaites. In accordance with this work, other reports have found higher resistance in wild genotypes compared with commercial cultivars (Thomazini et al, 2001;Proffit et al, 2011;Oliveira et al, 2012). Nonetheless, we here provide further information on the variability that can occur within a single genotype, depending on the accession tested, as we detected a wide range of larval survivals in the accessions of S. habrochaites (Table 2).…”
Section: Discussionsupporting
confidence: 91%
“…A considerable number of studies have described and investigated the resistance mechanisms of plants of the genus Solanum to disease-causing agents and insects (Kennedy, 2003); however, few studies have included Tuta absoluta. Hostplant resistance to tomato leaf miner has been reported for some host plants in the genus, such as Solanum pimpinellifolium, S. peruvianum, and S. habrochaites, compared with commercial tomato genotypes (Leite et al, 1995;Leite et al, 1999;Thomazini et al, 2001). A recent study demonstrated that genotypes that are produced with introgressions of the Ty-1 gene from S. chilense to S. esculentum confer resistance to the tomato leaf miner (Duarte et al, 2015), thus demonstrating the utility of investigating genotypic resistance mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Acredita-se que materiais resistentes não são atrativos ou são deterrentes para oviposição/alimentação dos ácaros, podendo não ser encontrados, ou mesmo encontrando-se alguns, estes realizam poucas posturas, como ocorreu no presente trabalho, pelo baixo número de ovos e fases imaturas verificados (Tabelas 1 e 2). De acordo com Williams et al (1980) essa não-preferência para oviposição está relacionada com a presença de tricomas que possuem o "inseticida natural" (2-tridecanona) produzido por tricomas glandulares do tipo VI. Ainda com relação ao PI 134417, Chatzivasileiadis & Sabelis (1997) verificaram em seus tricomas, elevada presença de metil cetonas, substân-cias altamente tóxicas a esses ácaros, sendo que, em L. esculentum foram encontrados menor número de tricomas com esse componente quími-co, o que indica ser necessário um maior contato do ácaro com mais tricomas para provocar a sua morte.…”
Section: Resultsunclassified
“…Porém, o fato de um genótipo ser selvagem não caracteriza que seja resistente, ou que possua algum tipo de resistência a determinada praga, o que foi evidenciado no presente experimento pela preferência do ácaro rajado para oviposição nos genótipos selvagens LA 1113-2 e LA 1113-1. Acredita-se que a suscetibilidade à oviposição desses genótipos possa estar relacionada com a ausência, ou a menor quantidade de tricomas glandulares, visto a importân-cia desses no fator resistência do genótipo PI 134417 observada por Williams et al (1980). Ainda com rela- ção ao LA 1113-1, a ocorrência de elevado número de fases imaturas, possivelmente, caracteriza a ausência ou a baixa concentração de componentes antibióticos, o que pode ter facilitado o desenvolvimento dessas fases.…”
Section: Resultsunclassified
See 1 more Smart Citation